Fundamentals of Software Engineering : 6th International Conference, FSEN 2015, Tehran, Iran, April 22-24, 2015. Revised Selected Papers - Dastani, Mehdi; Sirjani, Marjan; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the thoroughly refereed post-conference proceedings of the 6th IPM International Conference on Fundamentals of Software Engineering, FSEN 2015, held in Tehran, Iran, in April 2015. The 21 full papers presented in this volume were carefully reviewed and selected from 64 submissions. The topics of interest in FSEN span over all aspects of formal methods, especially those related to advancing the application of formal methods in software industry and promoting their integration with practical engineering techniques.
Towards Smart Systems of Systems -- Automated Integration of Service-oriented Software Systems -- Software Architecture Modeling and Evaluation Based on Stochastic -- Applicative Bisimulation and Quantum Lambda-Calculi -- A Theory of Integrating Tamper Evidence with Stabilization -- A Safe Stopping Protocol to Enable Reliable Reconfiguration for Component-based Distributed Systems -- Efficient Architecture-Level Configuration of Large-Scale Embedded Software Systems -- Benchmarks for Parity Games -- A behavioral theory for a pi-calculus with preorders -- Incremental Realization of Safety Requirements: Non-Determinism vs. Modularity -- Analyzing Mutable Checkpointing -- High Performance Computing Applications using Parallel Data Processing Units -- Improved Iterative Methods for Verifying Markov Decision Processes -- A Pre-congruence Format for XY-simulation -- Tooled Process for Early Validation of SysML Models using Modelica Simulation -- Can High Throughput Atone for High Latency in Compiler-Generated Protocol Code? -- Painless support for static and runtime verification of component-based Applications -- Linear Evolution of Domain Architecture in Service-Oriented Software Product Lines -- An Interval-Based Approach to Modelling Time in Event-B -- From Event-B Models to Dafny Code Contracts.
Keywords: Software engineering; Logic design; Artificial intelligence; Computer science; Software Engineering; Logics and Meanings of Programs; Artificial Intelligence; Programming Languages, Compilers, Interpreters; Programming Techniques